Autoimmune blistering skin diseases triggered by COVID-19 vaccinations: An Australian case series - Cowan, Timothy L.; Huang, Cheng; Murrell, Dédée F. (Frontiers in Medicine, 2023)
Autoimmune blistering skin diseases (AIBD) can be induced or flare from a multitude of sources, however there have been some reports of this occurring due to COVID-19 vaccinations. At a single academic blistering disease centre in Sydney, Australia, a retrospective review was conducted, identifying 59 patients with AIBD seen during February 2021 and November 2022. Secondary to recent COVID-19 vaccination, 4 patients had induction of bullous pemphigoid, 3 patients had a flare of pre-existing bullous pemphigoid, 1 patient had induction of pemphigus and 2 patients had a flare of pre-existing pemphigus vulgaris. This adds to our understanding of the role of vaccinations in the activity of AIBD.